Correction: Risk of colorectal cancer for carriers of a germ-line mutation in POLE or POLD1. (October 2018) - Buchanan, Daniel D; Stewart, Jenna R; Clendenning, Mark; Rosty, Christophe; Mahmood, Khalid; Pope, Bernard J; Jenkins, Mark A; Hopper, John L; Southey, Melissa C; Macrae, Finlay A; Winship, Ingrid M; Win, Aung Ko
The abstract to this article contained errors in the Results and Conclusions section. The corrected sections are shown below: